For the Record: Exploring variability in interpretations of police investigative interviews - Deamer, Felicity; et al. (Language and Law / Linguagem e Direito, 2022)
Recent research (Haworth 2018) has demonstrated how investigative interview data are (unintentionally) distorted as they pass through the criminal justice system, and the survey-based experiment we present here was designed to test our hypothesis that various aspects of the processing of police-suspect interview data may have an impact on the quality of the official evidential document produced. The quantitative and qualitative findings from this experiment shed light on, and provide a sound evidence base for this claim, rather than leaving it as an untested assumption. The experiment was designed to test each key aspect of the current process of the production of routine written transcripts of investigative interviews (ROTIs), focusing on the conversion from spoken to written format, and the use of different transcription conventions, and it has enabled us to investigate which changes make the most difference in terms of the evidential quality of the end product, in order to effect a change in practice which will reduce or eliminate the effect of those changes. Our findings suggest that when presented with a transcript of a police interview, we are significantly more likely to (1) perceive the interviewee as anxious and unrelaxed, (2) interpret the interviewee’s behaviour as being agitated, aggressive, defensive, and nervous, (3) determine that the interviewee is un-calm and uncooperative, and (4) deem the interviewee’s version of events to be untrue, than we are if we listen to the original audio recording. Moreover, subjects identified (a) consistency, (b) phrase and lexical choice, (c) emotion (crying/upset), (d) hesitation and/or pauses as significant factors influencing participants’ perception and interpretation of the interviewee and their story. This is particularly concerning as the latter two features are not currently routinely included in police transcripts, and Haworth (2018) illustrates multiple ways in which transcripts might differ from the original audio recordings they are intended to replace, with respect to words and phrases, as well as general content. The findings presented in this paper provide a strong motivation for further research into how we capture spoken interaction in legal contexts, and they constitute something of a mandate for reform with respect to the transcription of police interviews in the UK.